Deposit Insurance Database - Demirguc-Kunt, Asli (IMF Working Papers; Working Paper ;, 2014)
This paper provides a comprehensive, global database of deposit insurance arrangements as of 2013. We extend our earlier dataset by including recent adopters of deposit insurance and information on the use of government guarantees on banks' assets and liabilities, including during the recent global financial crisis. We also create a Safety Net Index capturing the generosity of the deposit insurance scheme and government guarantees on banks' balance sheets. The data show that deposit insurance has become more widespread and more extensive in coverage since the global financial crisis, which also triggered a temporary increase in the government protection of non-deposit liabilities and bank assets. In most cases, these guarantees have since been formally removed but coverage of deposit insurance remains above pre-crisis levels, raising concerns about implicit coverage and moral hazard going forward.